Contributions to the knowledge of the "Staphylinus-complex" (Coleoptera, Staphylinidae, Staphylinini) of China. Part 10. A new species of the genus Platydracus Thomson, 1858 - Smetana, Aleš (Zootaxa, 2005)
Platydracus juang Smetana, sp. nov., similar and closely related to the Japanese species Platydracus brachycerus Smetana & Davies, 2000, is described from one specimen taken in the province of Fujian.